Type and Gene Location of KIT Mutations Predict Progression-Free Survival to First-Line Imatinib in Gastrointestinal Stromal Tumors: A Look into the Exon - Incorvaia, Lorena (Cancers (Basel), 2021)
SIMPLE SUMMARY: Although effective in the majority of patients, the progression-free survival (PFS) to imatinib treatment can vary widely in effectiveness. Based on the known predictive role of tyrosine kinase (KIT) and platelet-derived growth factor receptor α (PDGRA) tumor genotypes, the differential clinical response to first-line imatinib treatment might be related to the different types and gene locations of the mutations. In our study, metastatic patients with gastrointestinal stromal tumors (GIST)-carrying KIT exon 11 deletion or a deletion/insertion involving codons 557/558 showed significantly shorter PFS to imatinib compared with those with deletion in codons other than 557/558 and patients with exon 11 duplication, insertion or single nucleotide variants (SNVs). Conversely, the latter subgroup showed the longest PFS first-line to imatinib. These results highlight the predictive role of pathogenic variant (PV) type and codon location in GIST, and can support stratification via mutational status in future clinical trials. ABSTRACT: In previous studies on localized GISTs, KIT exon 11 deletions and mutations involving codons 557/558 showed an adverse prognostic influence on recurrence-free survival. In the metastatic setting, there are limited data on how mutation type and codon location might contribute to progression-free survival (PFS) variability to first-line imatinib treatment. We analyzed the type and gene location of KIT and PDGFRA mutations for 206 patients from a GIST System database prospectively collected at an Italian reference center between January 2005 and September 2020. By describing the mutational landscape, we focused on clinicopathological characteristics according to the critical mutations and investigated the predictive role of type and gene location of the KIT exon 11 mutations in metastatic patients treated with first-line imatinib. Our data showed a predictive impact of KIT exon 11 pathogenic variant on PFS to imatinib treatment: patients with deletion or insertion/deletion (delins) in 557/558 codons had a shorter PFS (median PFS: 24 months) compared to the patients with a deletion in other codons, or duplication/insertion/SNV (median PFS: 43 and 49 months, respectively) (p < 0.001). These results reached an independent value in the multivariate model, which showed that the absence of exon 11 deletions or delins 557/558, the female gender, primitive tumor diameter (≤5 cm) and polymorphonuclear leucocytosis (>7.5 109/L) were significant prognostic factors for longer PFS. Analysis of the predictive role of PDGFRA PVs showed no significant results. Our results also confirm the aggressive biology of 557/558 deletions/delins in the metastatic setting and allow for prediction at the baseline which GIST patients would develop resistance to first-line imatinib treatment earlier.